Huata: chronological and architectural approaches of a settlement located in the upper Marañón (Huánuco) - Romero Rodríguez, Jakeline (2021)
Huata is an Archaeological Site located in the area known as Alto Marañón (Huánuco), and has brief references in the archaeological publications. Therefore, a way to approach its study was to characterize its chronology and architecture based on the analysis of the exposed structures, defining its typology, a comparative study will make with other sites in the area, especially Rapayán (Áncash) and Piruro (Huánuco); in addition, a review of the visit of Miguel de La Serna and Juan de Espinosa in 1549 will make. Consequently, this is a site with occupations from the Late Intermediate to the early Colonial Period, a historical process evidenced in the variability of its structures. Finally, the particular architectural and spatial configuration would suggest a dual organization, a recurrent characteristic of some social groups that occupied the Central Andes.